Tyrosine phosphorylation of Blk and Fyn Src homology 2 domain-binding proteins occurs in response to antigen-receptor ligation in B cells and constitutively in pre-B cells. - Aoki, Y (1994)
Proteins that bind to discrete domains of the Blk, Fyn, Lyn, and Btk protein tyrosine kinases were examined in pre-B cells that had not been subjected to any external stimulation, as well as in nonstimulated and antigen-receptor-ligated B cells. Proteins that bind to the Src homology 2 domains of Blk and Fyn were identified in B cells that had been activated with anti-IgM but were not identified in unstimulated B cells. A number of Blk and Fyn Src homology 2 domain-binding phosphoproteins were also observed in pre-B cells that had not been stimulated in vitro. The phosphoproteins seen in activated B cells potentially represent substrates that play a role in the pathway of antigen-receptor-mediated signaling. Distinct signaling pathways involving distinguishable kinase substrates may be relevant in pre-B-cell-receptor-mediated cell survival during ontogeny. These results indirectly support models that predict constitutive ligand-independent signaling by the pre-antigen receptor during lymphoid ontogeny.